2018
DOI: 10.1080/17425247.2018.1459559
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of a novel follitropin alfa pen injector: results from human factor interactions by patients and nurses

Abstract: The study provides valuable information on the pen from both patient and nurse perspectives in different simulated scenarios reflecting standard practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Another study, looking at the human factor interactions by patients and nurses for the Bemfola pen injector, used a list of pre-defined critical steps according to the IFU to assess the correct handling of the pen injector [20]. Interestingly, no critical errors related to the use of the pen injector were reported in this study and only minor issues were reported related to the priming of the pen injector.…”
Section: Discussionmentioning
confidence: 85%
“…Another study, looking at the human factor interactions by patients and nurses for the Bemfola pen injector, used a list of pre-defined critical steps according to the IFU to assess the correct handling of the pen injector [20]. Interestingly, no critical errors related to the use of the pen injector were reported in this study and only minor issues were reported related to the priming of the pen injector.…”
Section: Discussionmentioning
confidence: 85%
“…Studies showed that it has similar pharmacokinetics, efficacy and safety to the originator product (Gonalf ® , Merck Serono) ( 1 , 2 ). It is available as a prefilled single-use pen which provides a simple to-use alternative to other pens ( 4 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of ovarian stimulation regimens can lead to patient non-compliance ( 3 ), and easy-to-use devices could potentially help improve compliance with treatment. The Bemfola ® pen scored well in user acceptance studies ( 4 6 ).…”
Section: Introductionmentioning
confidence: 99%